Accuracy of instructor assessment of chest compression quality during simulated resuscitation. Issue 4 (18th January 2016) - Brennan, Erin E.; McGraw, Robert C.; Brooks, Steven C.
Abstract: Objectives: The 2010 American Heart Association Guidelines stress the importance of high quality cardiopulmonary resuscitation (CPR) as a predictor of survival from cardiac arrest. However, resuscitation training is often facilitated and evaluated by instructors without access to objective measures of CPR quality. This study aims to determine whether instructors experienced in the area of adult resuscitation (emergency department staff and senior residents) can accurately assess the quality of chest compressions as a component of their global assessment of a simulated resuscitation scenario. Methods: This is a prospective observational study in which objective chest compression quality data (rate, depth, and fraction) were collected from the simulation manikin and compared to subjective instructor assessment. Data were collected during weekly simulation training sessions for residents, medical students, and nursing students. Results: We included data from 24 simulated resuscitation scenarios assessed by 1 of 15 instructors. Subjective assessment of chest compression quality identified an adequate compression rate (100–120 compressions per minute) with a sensitivity of 0.17 (confidence interval [CI] 0.02–0.32) and specificity of 0.06 (CI −0.04–0.15), adequate depth (>50 mm) with a sensitivity of 0 and specificity of 0.38 (CI 0.18–0.57), and adequate fraction (>80%) with a sensitivity of 1 and a specificity of 0.25 (CI 0.08–0.42). Conclusion: Instructor assessment of chest compression rate, depth, and fraction demonstrates poor sensitivity and specificity when compared to the data from the simulation manikin. These results support the use of objective and technologically supported measures of chest compression quality for feedback during resuscitation education using simulators. RÉSUMÉ: Objectif: Dans les lignes directrices de 2010 de l'American Heart Association, on insiste sur l'importance de la qualité de la réanimation cardiopulmonaire (RCP) comme facteur prévisionnel de survie à un arrêt cardiaque. Toutefois, les séances de formation de réanimation sont souvent données et évaluées par des instructeurs, sans mesure objective de la qualité de la RCP. L'étude visait à déterminer si les instructeurs expérimentés dans le domaine de la réanimation chez les adultes (personnel au service des urgences, résidents séniors) pouvaient évaluer avec exactitude la qualité des compressions thoraciques, et ce, comme l'un des éléments de l'évaluation globale de scénarios de réanimation. Méthode: Il s'agit d'une étude d'observation prospective, dans laquelle il y a eu collecte de données objectives sur la qualité des compressions thoraciques (fréquence, profondeur, fraction) à partir de simulations sur mannequin, et comparaison avec l'évaluation subjective des instructeurs. Les données ont été recueillies durant les séances hebdomadaires de simulation, préparées à l'intention des résidents, des étudiants en médecine et des étudiants en soins infirmiers. Résultats: Les données recueillies provenaient de 24 séances de simulation de réanimation, et ont été évaluées par l'un des 15 instructeurs. Dans l'évaluation subjective de la qualité des compressions thoraciques, le caractère satisfaisant de la fréquence des compressions (100-120 compressions par minute) avait une sensibilité de 0, 17 (IC: 0, 02–0, 32) et une spécificité de 0, 06 (IC: −0, 04–0, 15); celui de la profondeur des compressions (>50 mm), une sensibilité de 0 et une spécificité de 0, 38 (IC: 0, 18–0, 57); et celui de la fraction (>80%), une sensibilité de 1 et une spécificité de 0, 25 (IC: 0, 08–0, 42). Conclusions: Il ressort de l'étude que l'évaluation de la qualité des compressions thoraciques par les instructeurs, quant à la fréquence, à la profondeur et à la fraction, avait une faible sensibilité et une faible spécificité, comparativement aux données recueillies par simulation sur mannequin. Aussi les résultats étayent-ils le recours à des mesures objectives de la qualité des compressions thoraciques et à des moyens technologiques appropriés dans la rétroaction donnée durant les séances de réanimation sur simulateur.